2016
DOI: 10.1002/prp2.225
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study on the incidence of severe photosensitivity reactions leading to hospitalization linked to topical ketoprofen and other medications in selected European regions

Abstract: The aim of this study was to assess the prevalence of exposure to topical nonsteroidal anti‐inflammatory drugs (NSAIDs), particularly ketoprofen, in a convenience sample of the population, to obtain estimates of the incidence of severe photosensitivity leading to hospitalization, and to assess causative factors in three catchment areas: the Paris metropolitan area, the Lombardy region (Italy) and the Prague area. All cases of severe photosensitivity not explained by underlying conditions and admitted to hospit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…One 55 showed that the reporting OR for topical ketoprofen was 3.9 (95% CI 2.4 to 6.4) and the proportional reporting ratio was 3.4 (95% CI 2.1 to 5.5), versus other topical NSAIDs. The other 56 reported that the overall population attributable risk (PAR) for severe photosensitivity reactions linked to topical ketoprofen was 11.92% (–0.12 to 52.99) and the PAR for other topical NSAIDs was 2.47% (–3.17 to 29.99). Another case-control study 57 showed that topical NSAIDs might decrease the risk of squamous cell carcinoma (ever use vs non-use, incidence rate ratio (IRR): 0.85, 0.76 to 0.94) and malignant melanoma (IRR: 0.87, 0.80 to 0.95).…”
Section: Resultsmentioning
confidence: 99%
“…One 55 showed that the reporting OR for topical ketoprofen was 3.9 (95% CI 2.4 to 6.4) and the proportional reporting ratio was 3.4 (95% CI 2.1 to 5.5), versus other topical NSAIDs. The other 56 reported that the overall population attributable risk (PAR) for severe photosensitivity reactions linked to topical ketoprofen was 11.92% (–0.12 to 52.99) and the PAR for other topical NSAIDs was 2.47% (–3.17 to 29.99). Another case-control study 57 showed that topical NSAIDs might decrease the risk of squamous cell carcinoma (ever use vs non-use, incidence rate ratio (IRR): 0.85, 0.76 to 0.94) and malignant melanoma (IRR: 0.87, 0.80 to 0.95).…”
Section: Resultsmentioning
confidence: 99%